MiR-23b-3p induces the proliferation and metastasis of esophageal squamous cell carcinomas cells through the inhibition of EBF3. (10th May 2018) - Zhang, Jing; Zhang, Yan; Tan, Xiaoping; Zhang, Qing; Liu, Chaoyong; Zhang, Yali
Abstract: MicroRNAs (miRNAs), some small non-coding RNAs that regulate gene expression at the posttranscriptional level, are always aberrantly expressed in carcinomas. In this study, we found that miR-23b-3p was remarkably up-regulated in human esophageal squamous cell carcinoma cells and tissues. Moreover, miR-23b-3p could induce the proliferation, invasion, and metastasis in vitro . EBF3 was identified as the direct downstream target gene of miR-23b-3p and ectogenic EBF3 could strongly inhibit the proliferation, invasion, and metastasis in vitro . Furthermore, it was found that miR-23b-3p could regulate epithelial-to-mesenchymal transition progress by blocking EBF3. Therefore, it was concluded that miR-23b-3p targeted EBF3 to accelerate the proliferation, invasion, and metastasis in ESCC.